Human-induced pluripotent stems cells as a model to dissect the selective neurotoxicity of methylmercury - Prince, Lisa M. (Biochim Biophys Acta Gen Subj, 2019)
Methylmercury (MeHg) is a potent neurotoxicant affecting both the developing and mature central nervous system (CNS) with apparent indiscriminate disruption of multiple homeostatic pathways. However, genetic and environmental modifiers contribute significant variability to neurotoxicity associated with human exposures. MeHg displays developmental stage and neural lineage selective neurotoxicity. To identify mechanistic-based neuroprotective strategies to mitigate human MeHg exposure risk, it will be critical to improve our understanding of the basis of MeHg neurotoxicity and of this selective neurotoxicity. Here, we propose that human-based pluripotent stem cell cellular approaches may enable mechanistic insight into genetic pathways that modify sensitivity of specific neural lineages to MeHg-induced neurotoxicity. Such studies are crucial for the development of novel disease modifying strategies impinging on MeHg exposure vulnerability.